2017
DOI: 10.14202/vetworld.2017.386-392
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Type I, predominant genotype isolated from sheep in South of Iran

Abstract: Aim:This study was performed to determine the genetic diversity of Toxoplasma gondii in sheep using nested-polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in Southern Iran.Materials and Methods:The tissue samples of diaphragm and heart from 125 sheep were collected from the main slaughterhouses of Jahrom district in South of Fars province, Iran, between Aprils and June 2013. The DNA were extracted and analyzed by nested-PCR using specific primers for SAG2 and GRA6 loci. RFLP was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…It has been reported that there is a correlation between of T.gondii genotype and clinical symptoms and pathogenesis pro le of parasite[29,30].Besides, it is veri ed that genotype I known as acutely virulent; whereasgenotype II and III are signi cantly less virulent that can establish latent toxoplasmosis[31].Due to speci c polymorphisms of GRA6 marker, it was selected in our study to genotyping of isolated T.gondii and at the next step PCR-RFLP test viaMseІ endonuclease was performed to discriminate between types I, II, and III[32].Nested-PCR of GRA6 gene for 10 tissue samples (7 sheep and 3 goats) was positive and RFLP technique approved all of them cluster into genotype І. These results are in agreement with two previous surveys of different parts of Iran[33,34].It is proven that predominant genotype in animal especially ruminants in Iran is genotype II; Whereas prior European investigation demonstrated the most predominant genotype belongs to type III[35].In our study, variables analysis in sheep and goats showed that infection rate of toxoplasmosis increased with age. This age-related variation can be due to the fact that older animals have been exposed to risk factors for a longer time.…”
supporting
confidence: 88%
“…It has been reported that there is a correlation between of T.gondii genotype and clinical symptoms and pathogenesis pro le of parasite[29,30].Besides, it is veri ed that genotype I known as acutely virulent; whereasgenotype II and III are signi cantly less virulent that can establish latent toxoplasmosis[31].Due to speci c polymorphisms of GRA6 marker, it was selected in our study to genotyping of isolated T.gondii and at the next step PCR-RFLP test viaMseІ endonuclease was performed to discriminate between types I, II, and III[32].Nested-PCR of GRA6 gene for 10 tissue samples (7 sheep and 3 goats) was positive and RFLP technique approved all of them cluster into genotype І. These results are in agreement with two previous surveys of different parts of Iran[33,34].It is proven that predominant genotype in animal especially ruminants in Iran is genotype II; Whereas prior European investigation demonstrated the most predominant genotype belongs to type III[35].In our study, variables analysis in sheep and goats showed that infection rate of toxoplasmosis increased with age. This age-related variation can be due to the fact that older animals have been exposed to risk factors for a longer time.…”
supporting
confidence: 88%
“…Diverse techniques for Toxoplasma genotyping have been created in the previous years (Liu et al 2009). Multilocus PCR-RFLP was the strategy for decision to recognize the genotypes of T. gondii isolates, for the most part for its effortlessness, great sensitivity and applicability (Armand et al 2017). It distinguishes between the three clonal genotypes of T. gondii adding to some atypical genotypes (Tavakoli Kareshk et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping can clear up the fundamental pathogenic components of an organism such as the virulence (Armand et al 2017). Previously, T. gondii strains have been characterized into three hereditary Types by their virulence impact on mice.…”
Section: Introductionmentioning
confidence: 99%
“…The parasite genotype and severity of clinical outcome in human toxoplasmosis cases are strongly related and in mouse model, type I is known to be more virulent compared to type II and type III [ 6 ]. It is recommended to type T. gondii isolates in clinical cases to assess the effect of genotype on the severity of toxoplasmosis [ 30 , 31 ]. However, available routine genotyping methods that are based on the detection of parasite DNA are not always adequate because the amount of parasite DNA present in the host/patient’s fluids or tissues is not necessarily present at detectable or sufficient levels for genotyping and subsequent analysis.…”
Section: Discussionmentioning
confidence: 99%